2020
DOI: 10.1021/acsenergylett.0c00831
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Onset of Lithium Plating and Monitoring Fast Charging Performance with Voltage Relaxation

Abstract: A key challenge for energy storage and conversion technologies is finding simple, reliable methods that can identify device failure and prolong lifetime. Lithium plating is a well-known degradation process that prevents Li-ion battery fast charging, which is essential to reduce electric vehicle “range anxiety” and enable emerging technologies such as aerial drones and high-performance portable electronics. The ability to detect the initial onset of lithium plating from easily accessible voltage measurements wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(89 citation statements)
references
References 35 publications
1
88
0
Order By: Relevance
“…OCV monitoring is a practical in situ Li plating detection method to examine the onset of Li plating and fast charging on a graphite anode in conventional Li-ion batteries. 34,35 Uhlmann et al rst reported a characteristic OCV prole aer charging; two potential plateaus for the plated Li and lithiated graphite (Li x C 6 ). 36 Schindler et al proposed a Li detection technique using the potential decay curve as a voltage derivative.…”
Section: Open-circuit Voltage Relaxation Before the 1 St -Step LI Stripping Behaviourmentioning
confidence: 99%
“…OCV monitoring is a practical in situ Li plating detection method to examine the onset of Li plating and fast charging on a graphite anode in conventional Li-ion batteries. 34,35 Uhlmann et al rst reported a characteristic OCV prole aer charging; two potential plateaus for the plated Li and lithiated graphite (Li x C 6 ). 36 Schindler et al proposed a Li detection technique using the potential decay curve as a voltage derivative.…”
Section: Open-circuit Voltage Relaxation Before the 1 St -Step LI Stripping Behaviourmentioning
confidence: 99%
“…However, fast charge can cause Li plating and then induce the formation of Li dendrite, which may trigger safety issues. [ 39‐42 ] Konz recently studied the effect of different charge rates of 2 C, 3 C and 4 C on the Li plating occurrence of LIBs with graphite, [ 43 ] and highlighted the application of a differential open‐circuit voltage analysis (dOCV) to detect when Li plating began during a single charge for room‐temperature fast charging. The result revealed that Li plating could be observed at the beginning of 75%, 50% and 25% SOC during charging process for 2 C, 3 C and 4 C charge rate, respectively, showing that high charge rate facilitates Li plating.…”
Section: Factors Causing or Influencing Lithium Platingmentioning
confidence: 99%
“…After fast charging to certain SOC, the dOCV profiles show an inflection point feature of onset of lithium plating. Reproduced with permission from Ref [43], Copyright 2020, American Chemical Society.…”
Section: Factors Causing or Influencing Lithium Platingmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of metallic Li on graphite anode surface has been shown to cause irreversible loss of Li inventory, leading to significant cell capacity fading. [ 3,14,15 ]…”
Section: Introductionmentioning
confidence: 99%